Tài Chính Toàn Diện và Dân Trí Tài Chính – Trường Hợp Nghiên Cứu tại Việt Nam - Nguyễn Ngọc, Duẩn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study evaluates the impact of financial literacy on people’s use of financial services, thereby affecting financial inclusion. By surveying 530 people using Fintech products and services, the author found that the "Financial Inclusion" and "Fintech Usability" factors are positively reflected by "Financial Literacy” and “Social Influence”. "Financial Inclusion" is also positively affected by the two factors, namely "Trust" and " Fintech Usability". Only the factor "Trust" is not affected by "Financial Intelligence", just as the factor "Trust" is not affected by "Social Influence". From the research results, the author provides some policy implications.